Manajemen Sumber Daya Manusia Dalam Perspektif Kemandirian Fakultas Kedokteran Swasta: Studi Kasus pada Medical Educational Unit (MEU) - Affandi Affandi (MEDIA MEDIKA INDONESIANA, 2013)
ABSTRACT The management of human resource in relation to private medical school independency: case study of medical educational unitsBackground: Most of the weaknesses of private medical schools in Indonesia are due to inappropriateness in the management of human resources. Medical Educational Unit (MEU) can be used to evaluate its role in the management of human resource. There is no information about what aspects of management in human resources have been implemented by MEU.Objection: To analyze the implementation of aspects contributed to the management of human resources by MEU.Method: This is a qualitative study to assess the implementation of the management of human resources in MEU. Data collected by in depth interview, observations, and document analysis in 4 (four) private medical schools in West Java. Data analysis was done by using koding, categorization and description.Results: The compensations for human resources in private Medical Schools in West Java is still inappropriate. Based on observations in the perspective of self-directing, self-motivating, self-regulating, self-supporting, self-assessing, and self-decision, this study showed the weaknesses in self-motivating, which can be seen in low level of achievement drive, commitment, inisiative, and optimism. Besides, there was no optimalization in the usefulness of information system technology.Conclusions and Suggestions: The perspective of to be autonomous in private medical schools in the aspects of MEU is still inappropriate. Therefore, the management of human resources in MEU is still to be increased.Keywords: MEU, Fakultas Kedokteran, ManajemenABSTRAKLatar belakang: Lemahnya kemandirian Fakultas Kedokteran (FK) Swasta di Indonesia umumnya berkaitan dengan lemahnya manajemen sumber daya manusia (SDM) dalam menyelenggarakan pendidikan. Salah satu aspek dalam manajemen pendidikan yang dapat dijadikan tolok ukur adalah peran Unit Pendidikan Kedokteran (Medical Education Unit/MEU) yang sudah dimiliki oleh setiap FK di Indonesia. Belum diketahui bagaimana manajemen SDM diimplementasikan oleh MEU.Tujuan: Menganalisis implementasi aspek-aspek yang berkontribusi terhadap manajemen SDM di MEU.Metode: Merupakan penelitian kualitatif dengan melakukan wawancara mendalam, observasi, dan analisis dokumen pada MEU di 4 FK Swasta di Jawa barat. Data dianalisis secara deskriptif.Hasil: Aspek kompensasi pada manajemen sumber daya manusia di FK Swasta di Jawa Barat masih kurang dari memadai. Ditinjau dari perspektif kemandirian perguruan tinggi swasta, yaitu dari aspek self-directing, self-motivating, self-regulating, self-supporting, self-assessing, dan self-decision, maka hasil pengamatan yang diperoleh adalah aspek self-motivating masih kurang memadai, hal ini terlihat dari tingkat achievement drive, komitmen, inisiatif dan tingkat optimisme yang dapat dikategorikan belum memuaskan. Penggunaan teknologi sistem informasi untuk mendukung proses pendidikan juga belum dilaksanakan secara optimal.Simpulan dan Saran: Perspektif kemandirian FK swasta dilihat dari aspek MEU masih sangat kurang, hal ini terlihat dari rendahnya tingkat achievement drive, komitmen, inisiatif maupun tingkat optimisme. Oleh karena itu, kemandirian FK swasta